2021
DOI: 10.1002/srin.202100452
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Structure–Property Relationship in Spheroidized C45EC Steel Using Full Phase Crystal Plasticity Numerical Simulations

Abstract: Herein, micromechanical simulations for three different states of spheroidized steel (C45EC) are conducted under quasi‐static tensile loading based on the actual texture and crystallographic orientation from electron backscatter diffraction (EBSD) data. Data denoising is conducted with MTex (open‐source Toolbox with MATLAB) for cleaning up the EBSD data. Crystal plasticity‐based full phase numerical simulations are performed on these constructed representative volume elements (RVEs) to analyze the local stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…Since the previous works have shown that the second phase inclusions are major players in defining the formability of the material [15,41,55], a special focus was given to them in this work. Previous work [51][52][53][54][55][56] shows that the morphology and distribution of the second phase inclusions dictate the formability limit and damage degradation in a material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the previous works have shown that the second phase inclusions are major players in defining the formability of the material [15,41,55], a special focus was given to them in this work. Previous work [51][52][53][54][55][56] shows that the morphology and distribution of the second phase inclusions dictate the formability limit and damage degradation in a material.…”
Section: Discussionmentioning
confidence: 99%
“…This noise was reduced using an intelligent algorithm implemented on the MTEX toolbox with MATLAB [40]. The procedural details of the EBSD data cleaning and the developed algorithm are published elsewhere [41]. Therefore, readers are encouraged to refer to that work for further details.…”
Section: Selection Of Area For Full Phase Simulationsmentioning
confidence: 99%
“…This large local microstructural heterogeneity yields significant local strain contrast during deformation. The microstructural distribution, grain size, material properties, and grain orientation are adopted from previously published work [39][40][41]. This article investigates different parameters for varying the overall number of grains, strain levels, and volume fractions.…”
Section: Numerical Simulation Modelmentioning
confidence: 99%
“…However, their use of a high-resolution CPFEM to model the influence of the particles can hardly be justified, as it was conducted without the spatial resolution of each particle and without GND mechanisms that would be expected for submicron secondary particles. Umar et al [25] used the DAMASK software for two-dimensional simulations of an SSRVE with cementite in spheroidised medium-carbon steels. Qayyum et al [26] discussed how to efficiently use as coarse a resolution as possible and thin three-dimensional RVEs to save computing time for particle distributions.…”
Section: Introductionmentioning
confidence: 99%